Math, asked by manideepdushetti, 1 year ago

solve this problem very urgent

Attachments:

Answers

Answered by Anonymous
16
good question bro

LHS=

sinA - cosA+1/sinA +cosA-1

=> we multipley cosA OK

=> cosA(sinA-cosA+1)/cosA(sinA+cosA-1)

=> cosA(sinA-cosA+1)/sinAcosA+cos²A-cosA

=> cosA(sinA-cosA+1)/1-sin²A-cosA+sinAcosA

=> cosA(sinA-cosA+1)/(1-sinA) (1+sinA)-cosA(1-sinA)

=> cosA(sinA-cosA+1)/(1-sinA) (1+sinA-cosA)

=>cosA/1-sinA

Divided by cosA and fond it

cosA
____
cosA
__________
1 sinA
___ _ ____
cosA cosA

=> 1/secA-tanA
heans prove
LHS=RHS.

_____swarnim__#####

Anonymous: hay this is helpful
Anonymous: mark me as brainlist
Anonymous: thanks
Similar questions